Формування маркетингової стратегії в антикризовому управлінні будівельним підприємством - Андрущенко, В. А. (Ways to Improve Construction Efficiency, 2013)
The article focuses on the role of marketing in the life support of the company and considers modern marketing strategies as important forms of organization activity that sets the behavior of firms in the market, can withstand a lot of negative environmental factors, help organization take most profitable market position and hold it.